2010
DOI: 10.1126/science.1188639
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity Conservation Research, Training, and Policy in São Paulo

Abstract: The BIOTA-FAPESP program is linking a decade of research on biodiversity into public policy in the state of São Paulo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 4 publications
0
62
0
15
Order By: Relevance
“…The Serra do Mar biological corridor was once a continuous forest landscape. With the aim of conserving and restoring the Atlantic forest, the protection of some SAF areas has been prioritized on the basis of the occurrence of certain target species and landscape structural features (Joly et al, 2010). From the results of our ongoing study, if confirmed by further surveys, three priority actions could complement these current scientifically based institutional initiatives by providing new executive insights for the Serra do Mar corridor.…”
Section: Conservation Policy Outcomementioning
confidence: 86%
“…The Serra do Mar biological corridor was once a continuous forest landscape. With the aim of conserving and restoring the Atlantic forest, the protection of some SAF areas has been prioritized on the basis of the occurrence of certain target species and landscape structural features (Joly et al, 2010). From the results of our ongoing study, if confirmed by further surveys, three priority actions could complement these current scientifically based institutional initiatives by providing new executive insights for the Serra do Mar corridor.…”
Section: Conservation Policy Outcomementioning
confidence: 86%
“…De acordo com Joly et al (2010), poucos projetos de conservação da biodiversidade no Estado de São Paulo focam as dimensões humanas da biodiversidade, indicando a priorização desta temática no fomento à pesquisa científica para o decênio 2011-2020. Diante disso, identificamos a importância das ações de educação ambiental voltadas ao público adulto para promover a conservação da espécie.…”
Section: Introductionunclassified
“…The conservation of biodiversity has been on the political agenda of many countries, since the Convention on Biological Diversity in 1992 (JOLY et al, 2010). Considering that the loss of habitat is the main threat to biodiversity, the most effective protection strategies seek to limit changes in land use in areas which are important for conservation, imposing limits on human actions (CHOMITZ, 2004).…”
Section: Introductionmentioning
confidence: 99%